Features of teacher’s reflection: Connection with personal and professional value orientations - A. К. Belolutskaya; I. S. Krishtofik; V. A. Mkrtchyan (Образование и наука)
Introduction. The development of professional reflection is determined by the nature of the activity in relation to which it is carried out. At the same time, teacher professional reflection is an effective resource for the development of educational activities. At the present stage, there is a wide variety of education models. Each educational model is characterised by its special values; reflection has its own special meaning, purpose, and result in a specific educational model.Aim. The current research aims to present the authors’ model for studying the features of teacher professional reflection; to discuss the results of testing this research model, which made it possible to draw a number of conclusions about the presence and nature of the relationship between the level of teacher professional reflection and their personal and professional values.Methodology and research methods. The present research is based on the activity approach, theoretical provisions on the structure and functions of reflection of activity, the meaning of reflection in various models of education, the types of professional pedagogical reflection. The research model is developed through the questionnaire method and the case method. The study involved primary and secondary school teachers of three educational complexes in Moscow (N = 63).Results. It has been established that the values of the life and professional plan of the subjects are consistent with each other, and professional actions are generally not related to the declared professional values. The authors confirmed the hypothesis that the reflection of positional type has a significant positive relationship between the degree of congruence between the values declared in the survey and those manifested in solving problematic professional situations and the level of development of reflection of these types.Scientific novelty lies in the development of a model for studying the features of professional reflection associated with the personal and professional values of the teacher. The results obtained in the course of its approbation can serve as a basis for understanding the mechanisms for the development of professional reflection of teachers in various models of education.Practical significance. The developed methodology for studying the features of professional reflection of teachers can be used for the further creation of the set of tools for self-assessment and the development of professional pedagogical competence, the core of which is pedagogical reflection.